Units and Constituency in Prosodic Analysis: A Quantitative Assessment. Issue 2 (3rd July 2017) - Wilson, Andrew
Abstract: Drawing on methods from quantitative linguistics, this paper tests the hypothesis that the intonation unit is a valid language construct whose immediate constituent is the foot (and whose own immediate constituent is the syllable). If the hypothesis is true, then the lengths of intonation units, measured in feet, should abide by a regular and parsimonious discrete probability distribution, and the immediate constituency relationship between feet and intonation units should be further demonstrable by successfully fitting the Menzerath-Altmann equation with a negative exponent. However, out of 16 texts from the Aix-MARSEC database, only six share a common probability distribution and only eight exhibit a tolerable fit of the Menzerath-Altmann equation. A failure rate of ≥50% in both cases casts doubt on the validity of the hypothesis.